CDP-Diacylglycerol Synthases (CDS): Gateway to Phosphatidylinositol and Cardiolipin Synthesis - Blunsom, Nicholas J.; Cockcroft, Shamshad (Frontiers in Cell and Developmental Biology, 2020)
Cytidine diphosphate diacylglycerol (CDP-DAG) is a key intermediate in the synthesis of phosphatidylinositol and cardiolipin. Both phosphatidylinositol and cardiolipin have highly specialised roles in cells. Phosphatidylinositol can be phosphorylated and these phosphorylated derivatives play major roles in signal transduction, membrane traffic and maintenance of the actin cytoskeletal network. Cardiolipin is the signature lipid of mitochondria and has a plethora of functions including maintenance of cristae morphology, mitochondrial fission and fusion and for electron transport chain super complex formation. Both lipids are synthesised in different organelles although they share the common intermediate, CDP-DAG. CDP-DAG is synthesised from phosphatidic acid and CTP by enzymes that display CDP-DAG synthase activities. Two families of enzymes, CDS and TAMM41, which bear no sequence or structural relationship, have now been identified. TAMM41 is a peripheral membrane protein localised in the inner mitochondrial membrane required for cardiolipin synthesis. CDS enzymes are ancient integral membrane proteins found in all three domains of life. In mammals, they provide CDP-DAG for phosphatidylinositol synthesis and for phosphatidylglycerol and cardiolipin synthesis in prokaryotes. CDS enzymes are critical for maintaining phosphoinositide levels during phospholipase C signalling. Hydrolysis of phosphatidylinositol (4,5) bisphosphate by phospholipase C requires the resynthesis of phosphatidylinositol and CDS enzymes catalyse the rate-limiting step in the process. In mammals, the protein products of two CDS genes (CDS1 and CDS2) localise to the ER and it is suggested that CDS2 is the major CDS for this process. Expression of CDS enzymes are regulated by transcription factors and CDS enzymes may also contribute to cardiolipin synthesis in mitochondria. Studies of CDS enzymes in protozoa reveal spatial segregation of CDS enzymes from the rest of the machinery required for both phosphatidylinositol and cardiolipin synthesis identifying a key gap in our understanding of how CDP-DAG can cross the different membrane compartments in protozoa and in mammals.